Corn physical characteristics on piglet performance - Diovani Paiano; Marcos Augusto Alves Silva; Marlon José Zanotto; Juliano Hideo Hashimoto; Ivan Moreira (Acta Scientiarum: Animal Sciences, 2023)
This study aimed to correlate the physical characteristics of ground corn, at different crushing intensities, with the zootechnical performance of piglets in the nursery phase. Forty piglets (20 castrated males and 20 females) with an initial average weight of 15.7±1.98 kg and final weight of 32.5±3.27 kg were used. They were subjected to the same type of experimental diet (4% of commercial premix for the phase, 29% of soybean meal, and 67% of ground corn), with the only difference being the corn grinding process. The corn used was fractionated into five portions, and each one of them was crushed in a hammermill equipped with a different screen hole diameter (2; 2.5; 3; 3.5 and 4 mm). Which resulted in ground corn with the following particle sizes (PS): 518, 580, 628, 706 and 740 μm, and the following corn geometric standard deviations (GSD): 1.72, 1.71, 1.75, 1.80 and 1.90, respectively. The piglets were distributed in a completely randomized design with five treatments and four replications, with the experimental units being formed by pens with two piglets each. There was no effect (p > 0.10) from grinding intensities on daily feed intake (DFI) and daily weight gain (DWG). Conversely, there was an effect (p < 0.10) from different grinding intensities on feed conversion (FC). The PS and GSD of both the corn and diet, as well as the corn fractions retained on the 4-, 2- and 1.2-mm test sieves showed positive correlations with FC (p < 0.05). On the other hand, the corn fractions retained on the 0.6-, 0.3- and 0.15-mm teste sieves showed negative correlations with FC (p < 0.05). The linear model was the one that fitted the estimated data into the data observed for FC. A corn PS reduction from 740 to 580 μm promoted a linear improvement in FC. The use of corn fractions, retained on the 1-, 2- and 0.3-mm test sieves, and the use of corn GSD and diet GSD as independent variables showed a higher R² than that obtained with the use of corn PS as an independent variable in linear equations for estimating FC.